Life cycle assessment of compressed air, vanadium redox flow battery, and molten salt systems for renewable energy storage - Manal AlShafi (14778373) (2021)
Energy storage systems critically assist in the implementation of renewable energy sources. However, greenhouse gas emissions associated with the energy storage methods have received insufficient attention, especially for arid climate implementation. This paper considers three energy storage techniques that can be suitable for hot arid climates namely; compressed air energy storage, vanadium redox flow battery, and molten salt thermal storage and performs a comprehensive life cycle assessment analysis to comparatively evaluate the environmental impacts per kWh of energy. The results show that, when solar photovoltaic electricity is stored, the redox-flow battery has the highest global warming potential, corresponding to 0.121 kg CO2 eq./kWh, whereas the molten salt has the least with a value of 0.0306 kg CO2 eq./kWh. In contrast, the lowest ozone layer depletion is observed for the compressed air storage unit with a value of 7.24×10−13 kg R11 eq./kWh. In sensitivity analysis, it is found that using solar photovoltaic electricity for the considered energy storage methods rather than grid electricity critically reduces the associated environmental impacts, emphasizing the importance of implementing more renewables in the grid mix. The global warming potentials of compressed air and vanadium redox flow battery decrease by 0.599 and 0.420 kg CO2 eq,/kWh, respectively in case photovoltaic electricity is stored instead of grid electricity. It is also found that the production stage of the storage systems accounts for the highest share of carbon footprint. Other Information Published in: Energy Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.egyr.2021.09.161